ANALYSIS OF THE POTENTIAL FOR DOUBLE TAXATION ON HOUSEHOLD ELECTRICITY CONSUMPTION WITH POWER ABOVE 6,600 VOLT-AMPERE REVIEWED FROM COMPLIANCE COSTS - Pratiwi, Dwi Septya; Saptono, Prianto Budi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
The change in nomenclature from Street Lighting Tax (PPJ) to Certain Goods and Services Tax on Electricity (PBJT-TL) is a form of reclassification and follow-up to the Decision of the Constitutional Court of the Republic of Indonesia Number 80/PUU-XV/2017. This change in terminology confirms that the PBJT-TL is a tax imposed on electricity consumption by end users. Household electricity consumption with power above 6,600 volt-ampere (VA) is subject to both the PBJT-TL (local tax) and Value-Added Tax (central tax). The purpose of this study is to analyze the potential for double taxation on the policy of imposing Value-Added Tax (VAT) and PBJT-TL. In addition, this study also aims to analyze the compliance costs of imposing VAT on electricity and PBJT-TL. This study uses qualitative methods with data collection techniques through literature review. This study uses the theory of national double taxation and cost of compliance. The results of the analysis show that there is double taxation on electricity consumption. This contradicts the general explanation in the HKPD Law, which is to harmonize the tax objects between central and local taxes so as to avoid duplication of tax collection. The phenomenon of double taxation on electricity consumption is examined from the perspective of compliance costs, namely fiscal costs, time costs, and psychological costs. Based on previous studies, VAT and PBJT-TL will increase the cost of electricity usage, and double taxation will also cause unfairness for taxpayers. This will result in tax compliance costs.